Assimilating Oxaliplatin (Eloxatin) into the Management of Colorectal Cancer (TAJ: Journal of Teachers Association, 2011)
Oxaliplatin (Eloxatin) is a third-generation platinum analogue which is a novel compound with proven anti-tumor activity in colorectal cancer. That has demonstrated synergy with 5-fluorouracil (5-FU) in human tumor xenograft models. A series of phase II trials demonstrated that, as second-line therapy, oxaliplatin in combination with 5-FU/leucovorin (LV) is active and can overcome clinical resistance to 5-FU. Subsequently, two large, randomized, phase III trials demonstrated that the addition of oxaliplatin to 5-FU/LV significantly improved response rates and time to disease progression in the first-line setting, but had no statistically significant impact on survival. Oxaliplatin in combination with 5-FU/LV represents an important treatment option for patients in whom 5-FU-based therapy has failed and as first-line therapy. Oxaliplatin has also been investigated in combination with the oral Fluoropyrimidine, capecitabine. As an oral agent that exploits the high intratumoral activity of thymidine phosphorylase to generate 5-FU preferentially within tumor tissue, capecitabine may improve the efficacy and tolerability of Fluoropyrimidine/oxaliplatin combination therapy. A phase I dose-escalation study has been performed in patients with advanced/metastatic solid tumors to establish the most appropriate regimen. The study indicated that the combination is feasible and has substantial antitumor activity in patients with colorectal cancer. This article provides an overview of the clinical trial data for oxaliplatin and discusses how oxaliplatin may best be used in the future.TAJ 2011; 24(1): 11-15